Prevalence of tobacco dependence and associated factors in China: Findings from nationwide China Health Literacy Survey during 2018-19 - Zhao Liu; Ying-hua Li; Zi-yang Cui; Li Li; Xue-qiong Nie; Cheng-dong Yu; Guang-liang Shan; Xin-mei Zhou; Rui Qin; An-qi Cheng; Kian Fan Chung; Zheng-ming Chen; et al. (Elsevier, 2022)
Summary: Background: Tobacco dependence is the key barrier to successful smoking cessation. However, little is known about its prevalence, sociodemographic characteristics and determinants. We aimed to estimate the prevalence, associated factors and burden of tobacco dependence in China. Methods: During 2018-2019, the nationally representative 2018 China Health Literacy Survey (2018 CHLS) invited 87,708 participants to participate using a multistage stratified sampling method from 31 provinces (or equivalent) in mainland China, and 84,839 participants aged 20-69 with valid data were included in the analysis. We diagnosed tobacco dependence based on international criteria (ICD-10, DSM-4) and tailored to Chinese population according to China Clinical Guideline for Tobacco Cessation (2015 version). The prevalence of tobacco dependence was estimated overall and by sociodemographic factors. The Logistic regression was conducted to estimate odds ratios (OR) and 95% confidence intervals (CIs) for tobacco dependence and success of smoking cessation (being ex-smokers), with different levels of adjustment. These were used to estimate the total number of adults who were tobacco dependent in China. Findings: In China, the estimated prevalence of current smoking was 25.1%, significantly higher in men than in women (47.6% vs 1.9%). The prevalence of current smoking varied approximately 3-fold (12.9% to 37.9%) across 31 provinces of China. Among general population aged 20-69 years, the prevalence of tobacco dependence was 13.1% (95% CI:12.2-14.1). Among current smokers, the prevalence of tobacco dependence was 49.7% (46.5-52.9%), with no difference between men and women (49.7% vs 50.8%). The prevalence of tobacco dependence was associated significantly with smoking intensity, defined by pack-years (1.62 [1.54-1.70] per 10 pack-years), cigarettes smoked per day (2.01 [1.78, 2.27] per 10 cigarettes), and smoking starting age (0.93 [0.90, 0.97] per 5 years). Given smoking intensity, the prevalence of tobacco dependence also varied by age, gender, certain socioeconomic status and regions. Compared with those without tobacco dependence, ever smokers with tobacco dependence were less likely to be ex-smokers (2.88, 2.59-3.21). In China, 183.5 (170.4-197.4) million adults (177.5 million were men) were tobacco dependent in 2018. Interpretation: In China, tobacco dependence is highly prevalent, with approximately half of current smokers being addictive, highlighting the need for coordinated effort to improve awareness, diagnosis and treatment of tobacco dependence. Funding: Chinese Academy of Medical Sciences (CAMS) Initiative for Innovative Medicine (CAMS 2021-I2M-1-010), National Key R&D Program of China (grant no 2017YFC1309400), and National Natural Science Foundation of China (grant no 81720108001). Note: Chinese translation of abstract is available in appendix section.